The association between rs7903146 polymorphism at the transcription factor 7-like 2 gene that regulates insulin and glucagon among type 2 diabetes mellitus patients - الطيلوني، آية محمد عزام زهير (2018)
Background: Genetic susceptibility has a crucial role in the etiology of type 2 diabetes mellitus (DM). This study aimed at studying the association between rs7903146C>T polymorphism in the transcription factor7-like 2 (TCF7L2) gene that spans 215.9 kb which consists of 17 exons and located at 10q25.3. Setting: A case control study Subjects and Methods: A total of 180 subjects were recruited between 2017-2018 (79 have type 2 DM, 41 were pre diabetic and 60 were control). Weight and height were measured and Body mass indexes were calculated (BMI). Glycosylated hemoglobin (HbA1C) was measured using Turbidimetric inhibition immunoassay (TINIA) for the in vitro determination. Genomic DNA was extracted from EDTA blood sample then TCF7L2 rs7903146C>T polymorphism was amplified by PCR and genotyped using Restriction Fragment Length polymorphism (RFLP) assay by RsaI restriction enzyme digestion and electrophoresed on agarose gel. Results: The mean HbA1c were 7.71%, 6.08% and 5.06% in type 2 DM, pre-DM and controls, respectively. Study showed that the highest frequencies were in the age group more than 50 years old (49.4% in DM, 43.9% in pre-DM and 33.3% in the control). Frequency of family history was higher in DM and pre- DM (94.9%, 63.4% ). TCF7L2 (rs7903146C>T) gene polymorphism among diabetes mellitus, pre-diabetes mellitus patients and controls three different genotypes (CC,CT,TT) and two alleles ( C,T) result that the higher significant of DM, pre-DM with control ( p-value <0.000). T allele shown higher significant (p=0.00082) ,in pre-DM CT vs CC give [OR 2.1, 95% CI :1.1 to 3.9,p-value 0.015] , TT vs CC [OR 0.8, 95%CI: 0.3 to 2.4, p-value 0.78] and T vs C [OR 1.2, 95%CI:0.7 to 2.2 ,p-value 0.46] while in DM CT vs TT [OR 4.1, 95%CI: 2.0-8.7 ,p-vale 0.0001] , TT vs CC [OR 8.9, 95%CI :2.9-27.1, p-value 0.0001] and T vs C [OR 2.7, 95%CI :1.6- 4.5, p-value 0.005]. Conclusion: TCF7L2 (rs7903146C>T) gene polymorphism is highly associated with pre-diabetes mellitus at CT genotype and diabetes mellitus type 2 at CT,TT genotypes ,T allele among Jordanian population.